Analysis on the Ecological Concept of Ternary Interactive Education in Business English Writing - Yuwan Zhang (Advances in Multimedia)
In order to improve the effect of business English writing education, this paper combines intelligent algorithms to study the ecological concept of ternary interactive education in business English writing and jointly identifies interference and source signals. Moreover, this paper derives the likelihood function of the received signal under the modulation mode of the interference and the source signal and jointly considers the information of the interference. The modulation recognition can well reduce the influence of interference on algorithm performance. In addition, this paper simulates the recognition performance of the likelihood function-based algorithm when the system has frequency offset and asynchronous time offset. Finally, this paper combines experimental research to verify that the business English education system based on the ternary interaction concept proposed in this paper can effectively improve the effect of business English writing education.